Integrasi Filsafat IPA dalam Asesmen Formatif dan Sumatif Melalui Perspektif Holistik - Putri, Shilfany; Lahabu, Yessika Destiana (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research theme is Integration of Natural Science (Natural Science) philosophy in assessment and summative through a holistic approach which not only views education as an aspect of knowledge but also views education in terms of skills, attitudes and values. A holistic approach prioritizes a balance between cognitive knowledge, practical skills and understanding of scientific values by emphasizing the importance of developing a scientific attitude, critical thinking and also the ability to collaborate and adapt to an ever-changing world. This research uses qualitative methods with interviews, observations and document analysis to collect data from science teachers in several elementary schools. The research results state that the integration of science philosophy in formative and summative assessments can enrich the evaluation process by assessing students' scientific thinking abilities, practical skills and scientific attitudes. Based on research findings, it is recommended to increase training for teachers and develop a curriculum that better supports holistic assessment